Automated radiolabelling of [68Ga]Ga-PSMA-11 (gallium (68Ga)-gozetotide) using the Locametz® kit and two generators - Elke A. van Brandwijk; Else A. Aalbersberg; Arman S. Hosseini; Alwin D. R. Huitema; Jeroen J. M. A. Hendrikx (SpringerOpen, 2024)
Abstract Background Steps have been taken by pharmaceutical companies to obtain marketing authorisation of PSMA ligands in the European Union. Since December 2022, Locametz® (PSMA-11, gozetotide) is licensed as kit for manual radiolabelling with gallium-68 and commercially available since mid-2023. The Summary of Product Characteristic (SmPC) describes manual radiolabelling with a maximum activity after radiolabelling of 1369 MBq. We aimed for radiolabelling with a higher activity to increase production efficiency, and thus, automated radiolabelling is strongly preferred over manual radiolabelling to reduce radiation exposure to personnel. The aim of this study was to develop and validate a method for automated radiolabelling of the Locametz® kit using ~ 2000 MBq of gallium-68 eluate for radiolabelling. Results Automated radiolabelling of [68Ga]Ga-PSMA-11 using the Locametz® kit provided a product which complies to the Ph. Eur., had a shelf-life of 6 h at room temperature, and theoretically reduced radiation exposure 5.7 times. Radiolabelling with one and two generator(s) resulted in a radiochemical yield of 91-102% and 96-101% after preparation, respectively. The radiochemical purity ranged from 98.0 to 99.6% for radiolabelling with one generator and ranged from 98.4 to 99.3% for radiolabelling with two generators with similar stability. The activity of the final product was much higher when using two generators, 1961-2035 MBq compared to 740-1260 MBq, which leads to ~ 1.5 times more patient syringes available per preparation. Conclusion Automated radiolabelling of [68Ga]Ga-PSMA-11 using the Locametz® kit with higher gallium-68 activity than specified in the SmPC results in a product that is in compliance with the Ph. Eur. monograph and has a shelf-life of 6 h at room temperature. Radiolabelling with two generators proved possible and resulted in a product with similar quality but with much higher efficiency.